2020
DOI: 10.14744/semb.2020.57259
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Anxiety and Depression Levels with Perceived Stress and Coping Strategies in Health Care Workers During The COVID-19 Pandemic

Abstract: Objectives: Coronavirus disease (COVID-19) has spread rapidly, locally and internationally after it started in Hubei province of China in December 2019. During the spread of this infectious disease in the world, health care workers are taking place as the main people in the screening and treatment of the disease. The present study aims to evaluate the relationship between anxiety and depression levels with perceived stress and coping strategies in health care workers during the COVID-19 pandemic. Methods: In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
29
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 37 publications
8
29
1
1
Order By: Relevance
“…As for the association between coping strategies and perceived stress, in both groups, resorting to emotion-focused coping strategies (acceptance, seeking emotional support, humor, positive reframing, religion) was negatively related to perceived stress, whereas the dysfunctional one was positively linked to stress. The first association we identified, according to which emotion-focused coping strategies are linked to lower level of perceived stress, thus functioning as a protective factor against negative psychological outcomes, is consistent with the results of many other studies on the general population during COVID-19 [106], as well as on HCWs before COVID-19 [107][108][109] and during it [110,111]. Similarly, also the second association we identified, according to which, on the contrary, dysfunctional coping strategies (behavioral disengagement, denial, self-blame, self-distraction, substance use) are linked to higher levels of perceived stress, is consistent with the results of many other studies [79,100,110], as well as in line with our expectations.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…As for the association between coping strategies and perceived stress, in both groups, resorting to emotion-focused coping strategies (acceptance, seeking emotional support, humor, positive reframing, religion) was negatively related to perceived stress, whereas the dysfunctional one was positively linked to stress. The first association we identified, according to which emotion-focused coping strategies are linked to lower level of perceived stress, thus functioning as a protective factor against negative psychological outcomes, is consistent with the results of many other studies on the general population during COVID-19 [106], as well as on HCWs before COVID-19 [107][108][109] and during it [110,111]. Similarly, also the second association we identified, according to which, on the contrary, dysfunctional coping strategies (behavioral disengagement, denial, self-blame, self-distraction, substance use) are linked to higher levels of perceived stress, is consistent with the results of many other studies [79,100,110], as well as in line with our expectations.…”
Section: Discussionsupporting
confidence: 89%
“…The first association we identified, according to which emotion-focused coping strategies are linked to lower level of perceived stress, thus functioning as a protective factor against negative psychological outcomes, is consistent with the results of many other studies on the general population during COVID-19 [106], as well as on HCWs before COVID-19 [107][108][109] and during it [110,111]. Similarly, also the second association we identified, according to which, on the contrary, dysfunctional coping strategies (behavioral disengagement, denial, self-blame, self-distraction, substance use) are linked to higher levels of perceived stress, is consistent with the results of many other studies [79,100,110], as well as in line with our expectations. Furthermore, consistently with the results of other works on Italian HCWs employed in facing COVID-19 during the first months of its spread [101,[112][113][114], we did not find positive associations between problem-focused coping strategies and stress reduction in both groups of HCWs.…”
Section: Discussionsupporting
confidence: 89%
“…These findings align with a multicenter study showing ED nurses preferred to cope by spending time with friends and family 13 . Another survey showed that for healthcare workers, relying on emotion-focused coping mechanisms may improve symptoms of anxiety and depression 26 . Furthermore, a 2020 scoping review on ameliorating interventions to reduce occupational stressors among ED staff indicated strategies such as mindfulness and relaxation aimed at ED healthcare workers reduced burnout, stress, and anxiety 27 .…”
Section: Discussionmentioning
confidence: 99%
“…The stress-response theory points out that when an individual is faced with a stressful event, the event will be perceived by the individual at first, and then the individual will make a preliminary assessment of the degree of stress caused by the stressful event, combine it with the experience and evaluation of other response resources, and finally produce corresponding coping behaviors [ 11 ]. Studies shows that positive and mature coping styles can improve the mental health of the general population [ 12 ]. Therefore, helping patients on MHD take an active response during the lockdown period to reduce the perceived stress has great significance in improving their mental health.…”
Section: Introductionmentioning
confidence: 99%